Deep brain stimulation of the subthalamic nucleus preferentially alters the translational profile of striatopallidal neurons in an animal model of Parkinson’s disease - Kamali Sarvestani, Iman; Visanji, Naomi P.; Creed, Meaghan C.; Shams Shoaei, Zahra; Nobrega, José; Hamani, Clement; Hazrati, Lili-Naz (Frontiers in Cellular Neuroscience, 2015)
Deep brain stimulation targeting the subthalamic nucleus (STN-DBS) is an effective surgical treatment for the motor symptoms of Parkinson's disease (PD), the precise neuronal mechanisms of which both at molecular and network levels remain a topic of debate. Here we employ two transgenic mouse lines, combining translating ribosomal affinity purification (TRAP) with bacterial artificial chromosome expression (Bac), to selectively identify changes in translational gene expression in either Drd1a-expressing striatonigral or Drd2-expressing striatopallidal medium spiny neurons (MSNs) of the striatum following STN-DBS. 6-hydroxydopamine lesioned mice received either 5 days stimulation via a DBS electrode implanted in the ipsilateral STN or 5 days sham treatment (no stimulation). Striatal polyribosomal RNA was selectively purified from either Drd2 or Drd1a MSNs using the TRAP method and gene expression profiling performed. We identified eight significantly altered genes in Drd2 MSNs (Vps33b, Ppp1r3c, Mapk4, Sorcs2, Neto1, Abca1, Penk1, and Gapdh) and two overlapping genes in Drd1a MSNs (Penk1 and Ppp1r3c) implicated in the molecular mechanisms of STN-DBS. A detailed functional analysis, using a further 728 probes implicated in STN-DBS, suggested an increased ability to receive excitation (mediated by increased dendritic spines, increased calcium influx and enhanced excitatory post synaptic potentials) accompanied by processes that would hamper the initiation of action potentials, transport of neurotransmitters from soma to axon terminals and vesicular release in Drd2-expressing MSNs. Finally, changes in expression of several genes involved in apoptosis as well as cholesterol and fatty acid metabolism were also identified. This increased understanding of the molecular mechanisms induced by STN-DBS may reveal novel targets for future non-surgical therapies for PD.